Unexpected Reactivity of Cationic-to-Cationic Thiolate Ligand-Exchange Reaction on Au25 Clusters - Lee, Donghoon (Langmuir : the ACS journal of surfaces and colloids, 2023)
Thiolate-protected molecular noble metal clusters have attracted significant attention due to their unique physicochemical properties, which make them applicable in diverse fields such as catalysis, sensing, and bioimaging. Ligand-exchange reactions are a crucial technique for synthesizing and functionalizing these clusters, as they allow for the introduction of new ligands onto the cluster surface, which can alter their properties. While numerous studies have investigated neutral-to-neutral, neutral-to-anionic, and neutral-to-cationic ligand-exchange reactions, the cationic-to-cationic ligand-exchange reaction has never been reported, making the study of such reactions intriguing. In this study, the cationic ligand-exchange reaction on Au25(4-PyET-CH3+)x(4-PyET)18-x (x ≈ 9) clusters, which contain both neutral and cationic ligands in nearly equivalent amounts, was investigated. Contrary to our expectation that the cationic-to-cationic ligand-exchange reaction would be suppressed due to Coulombic repulsion between the surface cationic ligands and incoming cationic ligands, the originally existing cationic ligand was selectively exchanged. The choice of counterions for cationic ligands played a crucial role in controlling the selectivity of ligand exchange. For instance, bulky and hydrophobic counterions such as PF6- can cause steric hindrance and reduce Coulombic repulsion, which promotes cationic-to-cationic ligand exchange. Conversely, counterions like Cl- can lead to neutral-to-cationic ligand exchange due to reduced steric hindrance and increased Coulombic repulsion between cationic ligands. These findings provide a novel method for tailoring the properties of molecular gold clusters through controlled ligand exchange without requiring the design of thiolate ligands with varying geometrical structures